Targeting Coagulase Activity in Staphylococcus aureus Bacteraemia: A Randomized Controlled Single-Centre Trial of Staphylothrombin Inhibition - Peetermans, Marijke; Liesenborghs, Laurens; Peerlinck, Kathelijne; Wijngaerden, Eric Van; Gheysens, Olivier; Goffin, Karolien E.; Hoylaerts, Marc F.; Jacquemin, Marc; Verhaegen, Jan; Peetermans, Willy E.; Verhamme, Peter; Vanassche, Thomas; for the Staphylothrombin Investigators (Thrombosis and Haemostasis, 2018)
Background Staphylococcus aureus (S. aureus) bacteraemia is frequent and carries a high morbidity and mortality. Coagulases secreted by S. aureus initiate blood coagulation by directly activating prothrombin. This pathogen-activated coagulation is insensitive to most antithrombotic drugs, with the exception of small molecule direct thrombin inhibitors (DTIs). DTIs inhibit the coagulase-prothrombin complex, or staphylothrombin, and improve outcome in preclinical models of S. aureus infection.Objective A single-centre, randomized, controlled feasibility and safety trial of staphylothrombin inhibition with DTIs in patients with S. aureus bacteraemia.Patients and Methods Consecutive eligible adult patients with S. aureus positive blood cultures in the University Hospitals Leuven (Belgium) were randomized 1:1 to DTI (oral dabigatran 110 mg twice daily or intravenous argatroban according to activated partial thromboplastin time [aPTT]) for 7 to 10 days, or subcutaneous enoxaparin 40 mg once daily. Primary outcomes were feasibility and safety of DTI in patients with S. aureus bacteraemia. Secondary outcomes include D-dimer evolution (day 0–4) as marker of coagulation activation; inflammatory and microbiological parameters; and clinical outcomes including metastatic infections.Results Thirty-one percent (94/303) of screened patients were enrolled. Dabigatran plasma levels inhibited staphylothrombin. Clinically relevant bleeding (5/47 vs. 5/47) and thrombotic (7/47 vs. 7/47) complications were similar in both groups. Coagulase inhibition with DTIs was associated with a trend towards faster D-dimer decrease at day 4 (–662 ± 249 ng/mL vs. –40 ± 213 ng/mL for DTI-treated patients vs. control; p = 0.06) and a numerically lower number of persistently positive blood cultures. No differences in inflammatory parameters or other clinical outcomes were observed.Conclusion Targeting staphylothrombin with DTIs is feasible in a subset of S. aureus bacteraemic patients, with comparable safety to standard thromboprophylaxis. In future studies of staphylothrombin inhibition, feasibility can be further improved by rapid diagnostics and by strategies without concomitant anticoagulant effect.
Keywords: anticoagulants; bacteraemia; coagulase; Staphylococcus aureus; thrombin